2012
DOI: 10.1186/1744-8069-8-74
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Basal Ganglia μ-Opioid Receptor Availability in Trigeminal Neuropathic Pain: A Pilot Study

Abstract: BackgroundAlthough neuroimaging techniques have provided insights into the function of brain regions involved in Trigeminal Neuropathic Pain (TNP) in humans, there is little understanding of the molecular mechanisms affected during the course of this disorder. Understanding these processes is crucial to determine the systems involved in the development and persistence of TNP.FindingsIn this study, we examined the regional μ-opioid receptor (μOR) availability in vivo (non-displaceable binding potential BPND) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…Selection of relatively healthy, opioid-dependent individuals does not represent BUP patients in clinical practice, and limits generalizability of research findings. Interestingly, patients with chronic pain who are not taking opioids exhibit lower μOR availability in pain-related brain regions than controls (Harris et al, 2007; DosSantos et al, 2012), which may reflect excess endogenous opioid release during persistent nociceptive signaling. It would be informative to ascertain whether chronic pain-related variations in endogenous opioid tone alter BUP-induced changes in μOR availability and/or clinical outcomes for opioid use or pain.…”
Section: Methodsmentioning
confidence: 99%
“…Selection of relatively healthy, opioid-dependent individuals does not represent BUP patients in clinical practice, and limits generalizability of research findings. Interestingly, patients with chronic pain who are not taking opioids exhibit lower μOR availability in pain-related brain regions than controls (Harris et al, 2007; DosSantos et al, 2012), which may reflect excess endogenous opioid release during persistent nociceptive signaling. It would be informative to ascertain whether chronic pain-related variations in endogenous opioid tone alter BUP-induced changes in μOR availability and/or clinical outcomes for opioid use or pain.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Reliable methods for quantification of [ 11 C]CFN binding are available, 3 and recent work suggests that the radiotracer binds preferentially to μ-opioid receptor subtype 1, compared 4 to subtype 2. Our physician colleagues have used [ 11 C]CFN to investigate the role of the μ-opioid system in tobacco smoking, 5 obesity and weight loss, 6 pain regulation as well as sex and genetic influences on these mechanisms, [7][8][9][10][11] social distress and reward, 12 drug addiction, 13,14 and migraine 15 and to understand emotion regulation and the pathophysiology and treatment responses in major depression. [16][17][18] We have also recently used [ 11 C]CFN to compare the effects of intranasal and intravenous administration of opioids in rhesus monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in positron emission tomography (PET) with [11C]carfentanil (CFN), a selective radiotracer for lORs, have demonstrated that there is a faulty lOR availability (nondisplaceable binding potential, BPND) in chronic trigeminal pain patients in vivo, 5 but information is still lacking regarding migraine. In this ª 2014 The Authors.…”
Section: Introductionmentioning
confidence: 99%